La constitucionalización del principio de confidencialidad y su regulación en el derecho administrativo peruano - Ríos Rengifo, Alex Junior (2024)
The present article addresses the issue in Peru regarding the excessive use of the right to access public information and the prejudice associated with confidentiality, which is often linked to corruption in public administration. Subsequently, a study on confidentiality is conducted from its broadest definition, and it is determined how it is regulated in the Peruvian legal system, with a constitutional and administrative approach. Finally, the importance of confidentiality in public administration is highlighted, as well as the need for it to be regulated as a principle in the Peruvian legal system.